Tingkat Partisipasi Olahraga Siswa Sekolah Dasar - Hisyam, Muhammad; Kristiyanto, Agus; Kardiyanto, Deddy Whinata (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aims to analyze sports participation among elementary school students in Karanganyar Regency, with a focus on comparing participation patterns between rural and urban areas. Materials and methods. A descriptive quantitative approach was employed, involving a sample of 180 students from six schools—three in rural areas and three in urban settings—spread across three districts in Karanganyar. Data collection utilized observation, questionnaires, and interviews, with the Sport Development Index (SDI) based on the 2007 SDI KK - OIR 2006 version and an adapted Physical Literacy Knowledge Questionnaire (PLKQ) as instruments. Data analysis was conducted using the SDI to examine the dimension of sports participation, with Microsoft Excel as the analysis tool. The participation index for elementary school students was 0.622, reflecting an average level of sports engagement across the sample. Results. According to the SDI norms, this indicates that weekly sports involvement among students falls within the moderate category. The findings highlight the need for targeted interventions to address disparities in sports participation, particularly between rural and urban areas. Conclusions. Overall, the sports participation of elementary school students in Karanganyar Regency shows that, according to the Sports Development Index (SDI) norms, their participation is included in the moderate category.